الأحكام الفقهية للاعلانات التجارية في مواقع التواصل الاجتماعي - حمادي أحمد رامي; بوخزة محمد الحسن (University of Eloued جامعة الوادي, 2024)
"تناولت هذه الدراسة موضوعاً مميزاً ومعاصراً يتعلق بالأحكام الفقهية المتعلقة بالإعلانات التجارية في مواقع التواصل الاجتماعي ، وكانت الإشكالية الأتية :كيف يمكن ضبط الإعلانات التجارية على مواقع التواصل الاجتماعي لتوافق أحكام الشريعة الإسلامية. ؟ وتناولنا في المبحث الأول بيان حقيقة ونشأة الإعلان ومراحل التطور التي مر بها. وفي المبحث الثاني أنواع وأهداف الإعلانات التجارية وفي المبحث الثالث الإعلانات التجارية مشروعيته وأحكامه وتوصلنا إلى النتائج الأتية: 1/ ضرورة مراقبة محتوى الإعلانات التجارية قبل نشرها في مواقع التواصل الاجتماعي من قبل الجهات الرقابية ومدى التزامها بأحكام الشريعة الإسلامية قبل وقوع الضرر فالواجب المبادرة بضبط كل مخالف وكل ما يضر الأفراد والمؤسسات . 2/ موضوع الإعلانات التجارية في مواقع التواصل الاجتماعي بحاجة لدراسات فقهية أكثر عمقا وقبل ذلك دراسات مسحية لمعرفة الواقع الموجود كي يتم التصور الكامل لهذا الموضوع المهم المستجد في عصرنا اليوم . 3/ العمل على تكثيف الحملات التوعوية من قبـل المؤسـسات الحكوميـة ووزارة الإعـلام، والمؤسسات الفكرية والثقافية والدينية حيال التعامـل مـع شـبكات ووسـائل التواصـل الاجتماعي عند نشر الإعلانات التجارية في مواقع التواصـل الاجتماعي . 4/العمل على إضافة الضوابط والقواعد الشرعية لاستخدام الإعلان التجاري في مواقـع التواصـل الاجتماعي في مناهج التدريس لكافة المراحل الدراسية وذلك لانتشارها . 5/إنشاء هيئات رقابية ، تقوم بممارسة الدور الرقابي على المحتـوى الموجـود فـي مواقـع التواصل الاجتماعي ، ومحاسبة وإيقاف المواقع التي تخالف الضوابط الشرعية.""This study dealt with a distinct and contemporary topic related to the jurisprudential rulings related to commercial advertisements on social networking sites, and the following problem was: How can commercial advertisements on social media sites be controlled to comply with the provisions of Islamic Sharia. ? In the first section, we discussed the truth and origin of the advertisement and the stages of development it went through. In the second section, the types and objectives of commercial advertisementsal . In the third section, commercial advertisements, their legitimacy and provisions We reached the following results: 1/ It is necessary to monitor the content of commercial advertisements before publishing them on social media sites by the regulatory authorities and the extent of their commitment to the provisions of Islamic Sharia before harm occurs. It is necessary to take the initiative to arrest every violator and everything that harms individuals and institutions. 2/ The issue of commercial advertisements on social media sites needs more in-depth jurisprudential studies and, before that, survey studies to know the existing reality in order to fully conceptualize this important topic emerging in our time today. 3/ Working to intensify awareness campaigns by government institutions, the Ministry of Information, and intellectual, cultural and religious institutions regarding dealing with networks and means of communication.Social media when publishing commercial advertisements on social networking sites. 4/Working to add legal controls and rules for the use of commercial advertising on social media sites Teaching curricula for all educational levels due to their spread. 5/ Establishing oversight bodies that exercise a supervisory role over the content on social media sites, and hold accountable and stop sites that violate Sharia controls."
Keywords: الاحكام الفقهية - الاعلانات التجارية - مواقع التواصل الاجتماعي; Jurisprudential Rulings - Commercial Advertisements - Social Media Sites